Stability Test of Acyclovir at Severe Conditions - Hamdi, A.; Fegas, R.; Berka, B.; Clarck, B.J. (Asian Journal of Chemistry, 2016)
In this paper, the influence of stability of acyclovir in severe conditions was tested (acid and alkaline environment) and the acyclovir impurities were evaluated using ion-pairing HPLC method and mobile phase H2O : ACN 5 : 95% (v/v) counter-ion C8H17SO4 Na 0.002 M, pH 2.5, KH2PO4 0.02 M, flow rate 1 mL/min, UV detection 253 nm. The method was precise and linear (R > 0.99985, n = 11) in the range of 1-100 μg/mL and reproducible (RSD = 2.65%).